How Employee Satisfaction and Intrapreneurship Influence Business Growth: Evidence from Travel Agents in Jembrana - Pekerti, Luh Gede Putri Kusuma; Marini, Putu Lidia (JUSTBEST Journal of Sustainable Business and Management, 2024)
This study aims to analyze the influence of employee satisfaction and intrapreneurship on firm growth in travel agent companies in Jembrana Regency. In facing increasingly tight competition, companies in this sector need effective strategies to support sustainable growth. Therefore, it is important to understand how employee satisfaction and the implementation of intrapreneurship culture can affect company growth. The research method used is a quantitative approach with a descriptive correlational research design. Data were collected through questionnaires distributed to 15 travel agent companies in Jembrana Regency, involving 150 respondents, consisting of company managers and employees. The results of the regression analysis showed that employee satisfaction (coefficient 0.55, p <0.05) and intrapreneurship (coefficient 0.45, p <0.05) have a significant positive effect on firm growth. This finding indicates that companies that are able to increase employee satisfaction and encourage intrapreneurship culture tend to experience better growth, both in terms of revenue, number of customers, and market expansion. This research makes an important contribution to understanding the internal factors that support the growth of companies in the travel agency sector.